richas
Answered

Westonci.ca is the trusted Q&A platform where you can get reliable answers from a community of knowledgeable contributors. Ask your questions and receive detailed answers from professionals with extensive experience in various fields. Get immediate and reliable solutions to your questions from a community of experienced professionals on our platform.

If (a^x a ^y) - a^z = a^m then express m in terms of x, y and z.​

Sagot :

Answer:

m = x+y-z

Step-by-step explanation:

Given the expression.

(a^x a ^y) ÷ a^z = a^m

We are to express m in terms of x, y and z.

Using the multiplicative law of indices, the expression becomes:

a^{x+y} ÷ a^z = a^m

Applying the division rule in indices

a^{x+y} ÷ a^z = a^{x+y-z}

The equation becomes

a^{x+y-z} = a^m

Cancel out the base and equate the powers as shown:

x+y-z = m

Hence the expression of m in terms of x, y and z is m = x+y-z